Clinicopathological significance of miR-27b targeting Golgi protein 73 in patients with hepatocellular carcinoma. Issue 2 (February 2019) - Liang, Hu; Ai-Jun, Ji; Ji-Zong, Zhang; Jian-Bo, Han; Liang, Zhao; Yong-Xiang, Yi; Chen, Yu
Abstract : Using five bioinformatics analysis software, we identified Golgi protein 73 (GP73) as a putative target of microRNA-27b (miR-27b), which is closely related to various biological processes or diseases such as bone metabolism disease, adipose cell and muscle cell development, pulmonary hypertension, cervical cancer, and breast cancer. However, the clinical significance of miR-27b in hepatocellular carcinoma (HCC) is still unclear. The differential expression of miR-27b in HCC and adjacent normal liver tissues was measured by quantitative reverse transcription PCR. Our results showed that the expression of miR-27b in tumor tissues is lower than that in adjacent nontumor tissues. The expression of miR-27b was significantly lower in HCC tissues with high expression of GP73, when compared with adjacent nontumor tissues. Moreover, down-regulated expression of miR-27b was closely correlated with serum GP73, tumor-node-metastasis stage, tumor size, and portal vein thrombosis. GP73 mRNA might be a target of miR-27b. The 5-year overall survival rate of the low miR-27b expression group was significantly lower than that of the high miR-27b expression group. Moreover, multivariate analysis of prognostic factors, with a Cox proportional hazards model, showed that low miR-27b expression was a significant and independent predictor of poor survival in HCC. Hence, the abnormal expression of miR-27b might be related to the occurrence and development of tumors. Similarly, a study in the Cancer Genome Atlas database demonstrated that the expression of miR-27b in 50 normal individuals was 1.6 times higher than that of 372 patients with liver cancer. The overall survival rate of the low GP73 expression group (275 liver cancer patients) was significantly longer than that of the high GP73 expression group (90 normal individuals). MiR-27b suppresses the expression of GP73 and is therefore a potential prognostic biomarker and therapy target in HCC.